502 CONTINUATION STUDY ON CARBON MONOXIDE EXPOSURE ON DENALI. Issue 1 (1st January 2007) - Johnston, E.; Sandven, T.; Roscoe, C.; Baker, E.
Abstract : Objective: This is a follow-up study to a similar study conducted in 2004 to further explore the potential relationship between elevated carboxyhemoglobin levels (COHb) and symptoms of acute mountain sickness (AMS) among climbers on at 4, 300 m on Denali. Additional analysis was performed to assess a potential relationship between COHb levels, AMS, and climber characteristics and behavior. Study Design: This study was conducted during the 2005 climbing season on Denali. Subjects were recruited at the advanced base camp (4, 300 m). Subjects were assessed for AMS symptoms by use of the Lake Louise Self-Report questionnaire and were asked about cooking and climbing behavior and history of previous altitude illness. Venipuncture was then performed, and the blood samples were analyzed for COHb content by cooximetry. Statistical analysis was then performed to assess possible relationships between COHb levels, AMS, and climber behaviors. Results: A total of 157 climbers participated in the study. There was no statistically significant relationship found between levels of carboxyhemoglobin and symptoms of AMS. Conclusions: Although a relationship was not found between AMS and levels of COHb, the project did serve to increase awareness among climbers and National Park Service staff about the potential dangers of CO exposure and the importance of ventilation while cooking in and near a tent.